The effect of artemisinin on the pH of plasmodium falciparum digestive vacuole - Ibrahim, Nadiah (2020)
Artemisinin, a highly potent antimalarial drug is widely used due to the rapid killing of Plasmodium parasites. However, artemisinin has been reported to have reduced susceptibility against P. falciparum in Southeast Asia demanding for new antimalarial drugs that have a similar mode of action with artemisinin. To date, the precise mechanism of action of artemisinin remains disputable despite decades of research. Recent evidence showed that artemisinin might have a direct inhibition of proton pump, V-type H+-ATPase located on the membrane of parasite’s digestive vacuole, in which the inhibition causes pH alteration in the acidic organelle. Hence, the pH of the digestive vacuole of parasites treated with artemisinin was measured in this study by using flow cytometry. The flow cytometry-based assay was optimised to measure the digestive vacuole pH using a ratiometric pH indicator, fluorescein isothiocyanate (FITC)-dextran loaded into the parasite’s digestive vacuole. A standard pH calibration curve is generated by using the isolated trophozoite stage parasites suspended in buffers with different pH in the presence of an ionophore, carbonyl-cyanide m-chlorophenylhydrazone (CCCP). Without CCCP, the steadystate digestive vacuole pH showed an acidic value of 5.42 ± 0.11. Next, the antimalarial activity of artemisinin was evaluated by using a 4-hour drug pulse assay to determine the 50% inhibitory concentration (IC50-4 hours) and sub-lethal concentrations (caused less than 25% parasite death). Mid ring stage parasites were pulsed with different concentrations of artemisinin (0-1000 nM) for 4 hours (mimic in vivo exposure) and then washed to remove the drugs. The parasite cultures were continually cultured for 24 hours to examine its growth and 48 hours to examine its viability. Sub-lethal concentrations (15 and 30 nM) were selected from this study to ensure the digestive vacuole pH change observed in the subsequent experiment was not due to parasite death. Using the similar assay of 4-hour drug pulse on mid ring stage parasites, the sub-lethal concentrations increased the digestive vacuole pH by 0.49 (15 nM, pH = 5.7 ± 0.1) and 1.56 pH unit (30 nM, pH = 6.77 ± 0.48), respectively as compared with the untreated parasites (pH = 5.21 ± 0.04). The same assay was performed at mid trophozoite stage parasites to enable direct measurement of the digestive vacuole pH. The pH of the digestive vacuole was increased by 1 (15 nM, pH = 6.6 ± 0.1) and 1.48 pH unit (30 nM, pH = 7.1 ± 0.08), respectively as compared with the untreated parasites (pH = 5.6 ± 0.1). A similar result of the digestive vacuole pH alteration caused by a standard V-type H+-ATPase inhibitor, concanamycin A was observed (pH = 7.4 ± 0.1). In conclusion, the result showed that artemisinin, like concanamycin A may inhibit the V-type H+-ATPase, which caused the pH alteration in the digestive vacuole. The flow cytometry-based assay in this study provides a simple and accurate model for the measurement of digestive vacuole pH with a simultaneous evaluation on parasite growth and viability following treatment with other antimalarial drugs.